Concise enantioselective synthesis of (+)-decarestrictine L via proline-catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination - Rawat, Varun; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-decarestrictine L, a cholesterol biosynthesis inhibitor metabolite, is described using a D-proline catalyzed sequential alpha-aminooxylation and a Horner-Wadsworth-Emmons olefination. (C) 2009 Elsevier Lid All rights reserved

Co(III)(salen)-catalyzed HKR of two stereocentered alkoxy- and azido epoxides: a concise enantioselective synthesis of (S,S)-reboxetine and (+)-epi-cytoxazone - Reddy, R. Santhosh; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Chavan, Vilas B.; Sudalai, Arumugam (Chemical Communications, 2010)
The HKR of racemic syn- or anti- alkoxy- and azido epoxides catalyzed by Co(salen) complex affords a practical access to a series of enantioenriched syn- or anti- alkoxy- and azido epoxides and the corresponding 1,2-diols. This strategy has been successfully employed in the concise, enantioselective synthesis of bioactive molecules such as (S, S)-reboxetine and (+)-epi-cytoxazone.

Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones